Carotid atherosclerosis in people of European, South Asian and African Caribbean ethnicity in the Southall and Brent revisited study (SABRE) - Anbar, Rayan; Chaturvedi, Nish; Eastwood, Sophie V.; Tillin, Therese; Hughes, Alun D. (Frontiers in Cardiovascular Medicine, 2023)
Background Atherosclerotic cardiovascular disease (CVD) risk differs by ethnicity. In comparison with Europeans (EA) South Asian (SA) people in UK experience higher risk of coronary heart disease and stroke, while African Caribbean people have a lower risk of coronary heart disease but a higher risk of stroke. Aim To compare carotid atherosclerosis in EA, SA and AC participants in the Southall and Brent Revisited (SABRE) study and establish if any differences were explained by established or novel CVD risk factors. Methods Cardiovascular risk factors were measured, and carotid ultrasound was performed in 985 individuals (438 EA, 325 SA, 228 AC). Carotid plaques, and intima-media thickness (cIMT) were measured. Associations of carotid atherosclerosis with ethnicity were investigated using regression analyses, with and without adjustment for potential confounders (age, sex) and mediators (education, diabetes, hypertension, total cholesterol, HDL-C, alcohol consumption, current smoking). Results: Prevalence of any plaque was similar in EA and SA, and lower in AC (17%, 17%, and 6% respectively; p < 0.001 by ANOVA). Total plaque area was also similar in EA and SA but reduced in AC, but there were no major differences in the maximum height or length of plaques in people with plaques by ethnic group. These ethnic differences were unaffected by adjustment for potential confounders or mediators. After adjustment for age and sex cIMT was higher in AC but this difference was attenuated by adjustment for CVD risk factors. Conclusions: Prevalence of carotid artery atherosclerotic plaques varies by ethnicity, independent of risk factors. The similarity of plaque burden in SA and EA despite established differences in CVD risk in these ethnic groups casts some doubt on the utility of carotid ultrasound as a means of assessing risk across ethnic groups.